Endocrine disruption by PFAS: a major concern associated with legacy and replacement substances - Panieri, Emiliano; Buha Djordjević, Aleksandra; Saso, Luciano (Archives of Pharmacy, 2021)
Per- and poly-fluorinated alkyl substances (PFAS) have been used for decades in a great variety of processes and products by virtue of their exceptional properties, versatility and chemical stability. Nevertheless, it is increasingly recognized that these substances can represent a serious hazard to human health and living organisms due to their persistence, long-range transport potential and tendency to accumulate in biota. For this reason, some efforts have been made across the EU to identify alternative molecules, with a shorter carbon chain and theoretically safer profile, that might replace the previous generation of legacy PFAS. Unfortunately, this strategy has not been entirely successful and serious concerns are still posed by PFAS in different human populations. Among others, an emerging aspect is represented by the adverse effects that both legacy and alternative PFAS can exert on the human endocrine system, with respect to vulnerable target subpopulations. In this review we will briefly summarize PFAS properties, uses and environmental fate, focusing on their effects on human reproductive capacity and fertility, body weight control and obesity as well as thyroid function.